Nickel-TiO2 nanotube anode for photo-electrolysers. (15th October 2016) - Pozio, Alfonso; Masci, Amedeo; Pasquali, Mauro
Highlights: We evaluated a composite nickel-TiO2 nanotube array anode for photo-electrolysis. We realized a composite multi-anode and we tested with direct solar light exposition in a small photo-electrolyser. A good solar conversion efficiency together with a reduction in energy demand was obtained. The system is able to work both in dark and under solar light exposure, opening new perspectives for industrial-scale applications. Abstract: This work evaluated a new combined electrode constituted by porous nickel and an array of highly ordered TiO2 nanotubes achieved by a former galvanostatic anodization treatment in an ethylene glycol solution. The photo-electrochemical response of the composite anode was appraised. It showed a mixed behaviour with interesting features with respect to its single components. Based on the characterization of the single electrode, a composite multi-anode has been realized and tested with direct sunlight exposition in a small photo-electrolyser. The system showed good solar conversion efficiency together with a reduction in energy consumption. The results highlighted that a photo-electrolyser, operating with a cell voltage of 2 V and with a correct insulation, guaranteed by an appropriate design and an optimal management of the gas products, could reduce by at least 3.5% its energy demand. Such a combination of materials makes the new system able to work both in dark and under solar light exposure, thus opening new perspectives for industrial-scale applications.